Island biogeography of insect conservation in urban green spaces - FATTORINI, SIMONE; MANTONI, CRISTINA; DE SIMONI, LIVIA; GALASSI, DIANA M.P. (Environmental conservation, 2018)
Because of their isolation, biotic communities of urban green spaces are expected to be similar to those of oceanic islands. This should be particularly true for insects, which represent an important component of urban faunas. The equilibrium theory of island biogeography (ETIB) allows for the formulation of some hypotheses regarding the influence of the geographical characteristics of green spaces on insect species richness and extinction risk. Based on island biogeography principles, we present eight predictions on how green space characteristics should influence insect species richness and loss. We analysed the current literature in order to determine which predictions were supported and which were not. We found that many studies gave outcomes that support ETIB predictions about the effects of area and isolation of green spaces; we found no strong support for predictions about shape and extent of native habitat in the literature that we reviewed. Most of the available studies dealt with patterns in species richness, whereas insect species loss has been rarely investigated. Future developments in the application of island biogeography principles to urban insect conservation should address temporal trends in species persistence and the analysis of species co-occurrence and nestedness.